Biomass fuel use and birth weight among term births in Nigeria. - Musa Abubakar Kana; Min Shi; Jennifer Ahmed; Jimoh Muhammad Ibrahim; Abdullahi Yusuf Ashir; Karimatu Abdullahi; Halima Bello-Manga; Matthew Taingson; Amina Mohammed-Durosinlorun; Musa Shuaibu; Abdulkadir Musa Tabari; Stephanie J London (Public Library of Science (PLoS), 2022)
Despite the high burden of household air pollution from biomass fuel in sub-Saharan Africa, the association of prenatal biomass fuel exposure and birth weight as a continuous variable among term births has not been extensively studied. In this study, our primary aim is to estimate the association between biomass cooking fuel and birth weight among term births in Kaduna, northwestern Nigeria. For replication, we also evaluated this association in a larger and nationally representative sample from the 2018 Nigerian Demographic and Health Survey (DHS). Our primary analysis included 1,514 mother-child pairs recruited from Kaduna, in northwestern Nigeria, using the Child Electronic Growth Monitoring System (CEGROMS). Replication analysis was conducted using data from 6,975 mother-child pairs enrolled in 2018 Nigerian DHS. The outcome variable was birth weight, and the exposure was cooking fuel type, categorized in CEGROMS as liquefied petroleum gas, kerosene, or biomass fuel, and in the DHS as low pollution fuel, kerosene, or biomass fuel. We estimated covariate adjusted associations between birth weight and biomass fuel exposure in CEGROMS using linear regression and using linear mixed model in the DHS. In CEGROMS, adjusting for maternal age, education, parity, BMI at birth, and child sex, mothers exposed to biomass fuel gave birth to infants who were on average 113g lighter (95% CI -196 to -29), than those using liquified petroleum gas. In the 2018 Nigeria DHS data, compared to low pollution fuel users, mothers using biomass had infants weighing 50g (95% CI -103 to 2) lower at birth. Exposure to biomass cooking fuel was associated with lower birth weight in our study of term newborns in Kaduna, Nigeria. Data from the nationally representative DHS provide some support for these findings.